2022
DOI: 10.3390/jcm11154607
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Computed Tomography Evaluation of Minimally Invasive Shaping Systems in Mandibular First Molars

Abstract: The aim of this study was to compare the shaping ability of a modified ProTaper Next technique (PTNm) with that of TruNatomy (TN) in lower molars mesial curved canals using micro-computed tomography (Micro-CT). Sixty mesial canals of first mandibular molars were randomly assigned between two groups (n = 30). After canal scouting with K-File #10, glide path and shaping were carried out with TN or PTNm systems. The PTNm sequence consists of ProGlider, followed by ProTaper Next X1 and apical finishing with NiTiFl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Also, TruNatomy produced less volume changes when compared to XP-Shaper, WaveOne Gold, Reciproc Blue, TRUShape and iRace [19,20]. Although, similar volume changes were observed when TruNatomy was compared to Vortex Blue, Edge le X3 and ProTaper Next [5,20,24]. Vortex Blue was found to have the same canal volume changes when compared to TRUShape, ProTaper Next and ProTaper Universal, but less volume changes when compared to XP-Shaper in oval canals [21,22,25].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Also, TruNatomy produced less volume changes when compared to XP-Shaper, WaveOne Gold, Reciproc Blue, TRUShape and iRace [19,20]. Although, similar volume changes were observed when TruNatomy was compared to Vortex Blue, Edge le X3 and ProTaper Next [5,20,24]. Vortex Blue was found to have the same canal volume changes when compared to TRUShape, ProTaper Next and ProTaper Universal, but less volume changes when compared to XP-Shaper in oval canals [21,22,25].…”
Section: Discussionmentioning
confidence: 73%
“…The changes in root canal surface area and canal volume after preparation with both VB and TN groups were similar with no signi cant differences. TruNatomy showed no signi cant differences in the changes in canal area after instrumentation when compared to Vortex Blue, ProTaper Next, XP-Shaper [5,19,24]. Although signi cantly less changes in canal surface area were observed when TruNatomy was compared to WaveOne Gold, Reciproc Blue, TRUShape and iRace [19].…”
Section: Discussionmentioning
confidence: 84%
“…The study compared a modified form of the ProTaper Next shaping technique (PTNm) with the TruNatomy (TN) regarding lower molar mesial curved canals. They found that these techniques were equally helpful in shaping the canals [26]. The use of micro-CT in comparing the intervention or diagnosis techniques is also reported by Alshehri et al [27] and Saberi et al [28].…”
Section: Introductionmentioning
confidence: 68%
“…On a further note, Berutti et al [26] described the usage of micro-CT in the assessment and comparison of marginally invasive systems for shaping in relation to mandibular first molars. The study compared a modified form of the ProTaper Next shaping technique (PTNm) with the TruNatomy (TN) regarding lower molar mesial curved canals.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of canal transportation made using micro-CT imaging have been increasingly used in endodontic research. This is a nondestructive, reproducible, and well-established method to assess the quality of the biomechanical shaping of new instruments and techniques engineered to facilitate the reduction of procedural errors (Hwang et al, 2014;Zhao et al, 2014;Pedullà et al, 2016;Yang et al, 2016;Brasil et al, 2017;Shah et al, 2017;Berutti et al, 2022). Freire et al (2012) compared two methods of assessing apical transportation in curved canals after rotary instrumentation, namely, cross sections and micro-CT.…”
Section: Discussionmentioning
confidence: 99%